Intervensi KKN-T untuk Pencegahan Stunting melalui Edukasi Gizi dan Ketahanan Pangan Lokal - Endi Rochaendi; Yusinta Dwi Ariyani; Ismanto Ismanto; Indah Perdana Sari; An Nisa Apriani; Ruwet Rusiyono; Suryandari Suryandari; Elvara Norma Aroyandini (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting remains a chronic nutritional problem that hinders human development in Indonesia due to its multidimensional impacts on cognitive aspects, economic productivity, and the social well-being of communities. To address this challenge, the Thematic Community Service program (KKN-T) of Alma Ata University in Debong Kulon Village was developed through a synergistic three-pillar model that integrates family nutrition education, literacy and utilization of local food, as well as household economic empowerment based on nutrition gardens as a holistic strategy to combat stunting. This program employs a community-based participatory approach through four systematic stages, problem identification, participatory planning, intervention implementation, and reflective evaluation, to ensure the program’s relevance and sustainability. Empirical results show a 23.5% increase in family nutrition knowledge, an 87% rise in participation in community health posts (posyandu), and 82% of households successfully managing nutrition gardens independently. Scientifically, these findings affirm the effectiveness of participatory communication, social learning, and local food self-sufficiency in fostering sustainable nutritional behavior change. The main conclusion indicates that the triple-pillar empowerment model has proven effective in strengthening social resilience and ensuring the sustainability of interventions, while also offering an adaptive replication model for urban and semi-urban areas within the framework of equitable and sustainable community development.